Innovative Barcode Scan Media for Cancer Education: Empowering Parents of Children Undergoing Chemotherapy - Faridah, Faridah; Mahyudin, Aulina; Setiadi, Setiadi; Kurniawan A, Zulkifli (http://dharmais.co.id/, 2025)
Background: Chemotherapy is a standard treatment for children with cancer, often accompanied by side effects such as nausea, vomiting, and hair loss. Parents require sufficient health education to manage their child’s treatment effectively. Previous methods lacked accessibility and engagement, which this study aims to address using digital technology. This study evaluates the impact of cancer treatment education using barcode scan media on the knowledge of parents with children undergoing chemotherapy at Dr. Soetomo Hospital. Method: This pre-experimental study used a one-group pretest-posttest design. A sample of 40 parents was selected via simple random sampling based on the following inclusion criteria: parents of children with cancer who were receiving chemotherapy, in good health, had provided informed consent, and owned an Android phone to access the barcode scan media. The exclusion criteria included parents who were ill or had children with complications. The intervention involved cancer treatment education through a barcode scan method, with knowledge measured using a questionnaire. Data were analysed using the Wilcoxon signed rank test, and SPSS software was used for statistical analysis.Results: Before the intervention, the mean knowledge score of parents was 7.65 (poor), which increased to 12.63 (good) after the intervention. The Wilcoxon signed-rank test showed a p-value of 0.000, indicating a statistically significant increase in parental knowledge. Conclusion: The study concluded that cancer treatment education through barcode scan media significantly improves parental knowledge regarding chemotherapy, offering a modern, accessible, and effective tool for health education. This method enhances understanding and management of chemotherapy side effects, leading to better child care outcomes.